The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.24136/oc.2021.017
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the CEO media coverage on corporate brand equity: evidence from Poland

Abstract: Research background: Despite increased attention in the literature to the importance of the CEO?s brand for companies, understanding of the effect of the CEO brand on the corporate brand remains limited. To contribute to this discussion, this paper investigates different facets of the impact of the CEO brand, and particularly its media coverage, on corporate brand equity. Purpose of the article: This study investigates the relationship between the different aspects of the CEO brand?s media coverage and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 54 publications
0
7
0
1
Order By: Relevance
“…In addition to media exposure at the firm level, as the policymakers and executors of enterprises, media exposure of TMTs also influences corporate business behaviours ( Górska and Mazurek, 2021 ). The CEO’s image may indirectly affect the image of the enterprise products ( Alghawi et al, 2014 ).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…In addition to media exposure at the firm level, as the policymakers and executors of enterprises, media exposure of TMTs also influences corporate business behaviours ( Górska and Mazurek, 2021 ). The CEO’s image may indirectly affect the image of the enterprise products ( Alghawi et al, 2014 ).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…From the external effect perspective, the entrepreneur's visibility can improve the internal and external business environment, so that enterprises can timely obtain the legal recognition and support of stakeholders, improving corporate risk-taking ability (Zhang and Han, 2020); Secondly, from the positive psychology perspective, entrepreneurs' visibility not only builds their personal brand but also intangibly enhance its brand value (Liu et al ., 2018). Gorska and Mazurek (2021) found that media coverage has a significant impact on the firm's brand equity, the entrepreneur's personal brand as an intangible resource can add more value for the firm.…”
Section: Introductionmentioning
confidence: 99%
“…These include, among others, credibility, influence [15], self-realization [16], reflexivity [17], differentiation in the market, employability [18,19] and monetary outcomes. Attempts are also being made to build Personal Brand Equity models [20] and in particular CEO Brand Equity [21][22][23][24]. The process of personal branding itself is reduced in the literature to the identification of general stages, which can be put down to [12]: raising self-awareness, analyzing audience needs and positioning, constructing brand architecture, seeking feedback and self-reflecting.…”
Section: Introductionmentioning
confidence: 99%